A Stylistic Analysis of Ayu Utami's Saman - Bambang, Widiatmoko; Pauzan, Haryono (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Ayu Utami is one of the most prominent contemporary Indonesian female writers. Her novel, Saman, which was first published in April 1998 was seen as one of the breakthroughs in the history of modern Indonesian literature. This novel describes Indonesian people who are undergoing changes at the cultural and political levels. So far, there have been studies on Ayu Utami's Saman by researchers.